Reconfigurable emergent patterns in active chiral fluids - Zhang, Bo; Sokolov, Andrey; Snezhko, Alexey (Nature communications, 2020)
Active fluids comprised of autonomous spinning units injecting energy and angular momentum at the microscopic level represent a promising platform for active materials design. The complexity of the accessible dynamic states is expected to dramatically increase in the case of chiral active units. Here, we use shape anisotropy of colloidal particles to introduce chiral rollers with activity-controlled curvatures of their trajectories and spontaneous handedness of their motion. By controlling activity through variations of the energizing electric field, we reveal emergent dynamic phases, ranging from a gas of spinners to aster-like vortices and rotating flocks, with either polar or nematic alignment of the particles. We demonstrate control and reversibility of these dynamic states by activity. Our findings provide insights into the onset of spatial and temporal coherence in a broad class of active chiral systems, both living and synthetic, and hint at design pathways for active materials based on self-organization and reconfigurability. Chiral active particles are known to exhibit intriguing emergent patterns of collective motion. Here, the authors employ pear-shaped Quincke rollers to generate reversible transitions between different states of collective motion by varying the strength of the applied electric field.